CONSIDERATION UPON THE PROTECTION OF THE HUMAN RIGHTS - Gheorghe , BORȘA (International Journal of Legal and Social Order, 2022)
The purpose of the present article is to bring general information connected to the human rights. We all know the fact that in the traditional international law, the protection of the human rights through international actions was not to be found. The concept of the international law of the human rights appears only in the second half of the 20th century, and thus matters connected to acknowledging and respecting them become problems of international interest and they do not depend exclusively only on the internal jurisdiction of the states. Romania admitted, appreciated and regulated the citizen’s rights as well as the theories that argumented their existence and also it has ratified the majority of the universal and European treaties concerning the human rights.